Rancang Bangun Sistem Pengukuran Alat Thermobath sebagai Alat Kalibrasi Temperatur dengan Sistem Arduino Uno - Yogatama Wishnu Pandu Prayudha; Sayid Fadhil; Sentot Novianto (Fakultas Teknik Universitas Pancasila, 2022)
A thermobath cooler is a device that contains water or other liquid as a coolant that can maintain a constant temperature. The control system designed in this study uses a K-type thermocouple temperature sensor and pressure transmitter microcontroller-based, namely Arduino Uno to be able to produce temperature and pressure measurement data on the thermobath through the software PLX-DAQ. This system thermobath requires a K-type thermocouple component and apressure transmitter JYB-KO-H. Before being placed in the system thermobath, the K-type thermocouple and pressure transmitter are required to calibrate. Based on the results of the temperature and pressure calibration equation, the coefficient of determination (R2) on the K-type thermocouple ranges from 0.9986 to 0.9998 and the coefficient of determination (R2) at the pressure transmitter is 0.9994. With the calibration results, the design of measuring thetool thermobath as a temperature calibration tool with the Arduino system can be applied to thecooling system thermobath.